The reasons for its effectiveness, however, remain in dispute—A tribute to Irving Kirsch - Gaab, Jens (Frontiers in Psychology, 2022)
Irving Kirsch’s work spans over four decades and provided science and clinical practice with as much invaluable insights in the inner workings of treatments as it provided us and patients with their rights and our duties. Here, two early publications of Irving Kirsch on the topic of psychotherapy and its relation to placebo are revised and put into both a historical and contemporary context to pay tribute to the work of Irving Kirsch.